Couples in the Qur'an (Comparative Study of the Interpretation of Ash-Sya'rawi and Hamka) - Asyifa Faradita; Muhammad Irsad; Muhammad Nur Amin (Quality : Journal Of Education, Arabic And Islamic Studies, 2023)
In general, many people think that a spouse must be (commensurate), as Allah says in Q.S. an-Nur verse 26, women are bad for bad men, good women for good men. But in the reality of life it is not all so, there are bad women get good male partners, and good women get bad male partners. Judging from the context of the verse, there are indeed differences in interpretation among the interpreters. Because of these differences in interpretation, in this study the author used a comparative method or the so-called comparison method. This research is new and different from the previous because there has been no research that discusses and compares the interpretation of ash-Sha'rawi and Hamka in Q.S. an-Nur verse 26 and looks for what are the factors behind the difference in interpretation between the two. After analysis, in his tafseer ash-Sha'rawi related the verse to a partner. He said that the verse is the same as Q.S. an-Nur verse 3, that a person will be paired with another person who is equal to himself. While Hamka in his tafseer explains that the verse relates to the hadith al-Ifk (fake news). This verse was revealed to clear the bad accusation against 'Aisha, i.e. accused of having an affair with Safwan ibn al-Mu'att}al. For it is impossible for 'Aisha, a very noble wife of the Prophet, to commit such a filthy deed as alleged.